(untitled) - McCleskey, Scott (Hoboken, N.J., 2010)
Authoritative guidance for navigating inevitable financial market regulation The reform of this country's financial regulation will be one of the most significant legislative programs in a generation. Financial Regulation and The Markets: A Guide to Understanding Today's Environment outlines everything you need to know to stay abreast of these changes. Written by Scott McCleskey, a Managing Editor at Complinet, the leading provider of risk and compliance solutions for the global financial services industry. Looks at the intended result of these regulations so that institutions and individuals will have a greater understanding of the new regulatory environment. Offers a realistic look at how these regulations will affect anyone who has a bank account, a car loan, a mortgage or a credit card. Covers the reforms that have been enacted and looks forward to future reforms. Both theoretical and practical in approach, Financial Regulation and the Markets provides a strong overview of coming regulation laws with insightful analysis into various aspects not easily understood.
Keywords: Financial institutions,Tổ chức tài chính; State supervision,Giám sát nhà nước; United States,Hoa Kỳ